2017
DOI: 10.2147/ott.s134915
|View full text |Cite
|
Sign up to set email alerts
|

<em>Foxj2</em> overexpression is associated with poor prognosis, progression, and metastasis in nasopharyngeal carcinoma

Abstract: Foxj2, a novel member of Forkhead box family, has been reported to play an important role in tumorigenesis, progression, and metastasis of certain cancers. However, the expression status and effects of Foxj2 on nasopharyngeal carcinoma (NPC) progression and metastasis remain debated. In this study, we first examined the expression of Foxj2 in NPC by immunohistochemistry and Western blotting analysis. We confirmed significantly elevated expression of Foxj2 in NPC tissues and cell lines. Next, the relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Nonetheless, Shan et al found that downregulation of FOXJ2 decreased the cell population in the S phase with enhanced G1 cycle arrest in nasopharyngeal carcinoma CNE-2 cells, and confirmed that patients with FOXJ2 overexpression had shorter survival in nasopharyngeal carcinoma. [ 15 ] In the current study, Kaplan–Meier survival analysis revealed that the high-FOXJ2 expression group showed longer median OS and PFS compared with the low-FOXJ2 expression group. Similar findings were obtained in the FIGO III-IV subgroup in stratified analysis.…”
Section: Discussionmentioning
confidence: 57%
“…Nonetheless, Shan et al found that downregulation of FOXJ2 decreased the cell population in the S phase with enhanced G1 cycle arrest in nasopharyngeal carcinoma CNE-2 cells, and confirmed that patients with FOXJ2 overexpression had shorter survival in nasopharyngeal carcinoma. [ 15 ] In the current study, Kaplan–Meier survival analysis revealed that the high-FOXJ2 expression group showed longer median OS and PFS compared with the low-FOXJ2 expression group. Similar findings were obtained in the FIGO III-IV subgroup in stratified analysis.…”
Section: Discussionmentioning
confidence: 57%
“…FOXJ2 overexpression is associated with poor prognosis, progression, and metastasis in nasopharyngeal carcinoma [ 95 ]. FOXQ1, a member of the FOX family, is overexpressed in colorectal cancer, and it enhances tumorigenicity and tumor growth [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…The (FOX) family comprises a set of evolutionarily conserved transcriptional regulatory factors (Shan et al 2017) and is involved in the regulation of various biological processes; it can be classi ed into categories A-S based on sequence similarity in mammals (Bademci et al 2019;Zhang et al 2017). In addition, the Fox family regulates gene transcription.…”
Section: Introductionmentioning
confidence: 99%